Paradise Lost, Sanity Gained: Towards a Critical Balinese Urbanism - Alexander R. Cuthbert (Jurnal Kajian Bali (Journal of Bali Studies), 2012)
AbstractBali is a global tourist destination having had the added descriptor paradise for most of the last century. But it is now transparent to most visitors that serious problems prevail across the entire local economy and built environment. The incoherence of development is largely to blame. Given the failure to generate a new Balinese architecture that matches the integrity of the old, Balinese urbanists are now caught in a Gordian knot where a unified traditional architecture remains, yet a new architecture is not forthcoming. How to untie the knot is the question. Architecture suffered major discontinuity when traditional building was largely abandoned in the face of progressive urbanization. The problem remains unresolved. The following paper represents a preliminary attempt to expose key issues. It suggests methods of moving forward. But a new momentum demands a new philosophy in the realm of urban theory, the foundation of all professional activity. No significant progress can take place without it. My attention is therefore directed to answering the question how can the transition be made from traditional Balinese architecture emerging from the dynamics of feudalism, to its conscious translation and accommodation within post-modernity, informational capitalism, and globalization? While the problem needs tackled at several levels – education, policy, strategy and enforcement, I suggest in conclusion that these should be framed within generic principles derived from vernacular transformations, a culture of critical Balinese regionalism, and an adaptation of the New Urbanist lexicon to a tropical environment.